Simplify.
(y 3)5 · y 4

(y^3)^5 * y^4 = y^15 * y^4; = y^19

s

Rating

There are no new answers.

Find the product.
(-4·3·2)2

Question

Updated 5/7/2015 8:19:48 AM

1 Answer/Comment

(-4·3·2)^2

= ((-12)(2))^2

= (-24)^2

= 576

= ((-12)(2))^2

= (-24)^2

= 576

Added 5/7/2015 8:19:48 AM

This answer has been confirmed as correct and helpful.

Find the product.
(y 2)5 · y 8

Question

Updated 5/8/2015 7:14:20 AM

1 Answer/Comment

(y^2)^5*y^8

= y^10*y^8

= y^18

= y^10*y^8

= y^18

Added 5/8/2015 6:57:41 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/8/2015 7:14:09 AM]

31,915,065

questions answered

There are no comments.